Specific circulating neutrophils subsets are present in clinically stable adults with cystic fibrosis and are further modulated by pulmonary exacerbations - Martin, Clémence; Dhôte, Théo; Ladjemi, Maha Zohra; Andrieu, Muriel; Many, Souganya; Karunanithy, Vaarany; Pène, Frédéric; Da Silva, Jennifer; Burgel, Pierre-Régis; Witko-Sarsat, Véronique (Frontiers in Immunology, 2022)
The progressive lung destruction in cystic fibrosis (CF) is tightly associated with chronic bacterial infection and neutrophil-dominated airway inflammation. CF pulmonary disease is complicated by episodes of acute exacerbations, contributing to irreversible lung damage. We hypothesized that circulating subsets of neutrophils from clinically stable adults with CF present some phenotypic specificities that could amplify their activation during an infectious episode. The aim of the present study was to examine the different neutrophil subsets in whole blood and in the low density neutrophils (LDN) that co-purify with peripheral blood mononuclear cells (PBMC) in clinically stable adults with CF and in CF adults during pulmonary exacerbations compared to healthy donors. Blood samples were obtained from 22 adults with CF (16 in stable state and 6 during pulmonary exacerbations) and from 20 healthy donors. Flow cytometry analysis of 13 different markers related to lineage (CD45, CD15), maturity (CD16, CD10, and CD33), activation (CD62L, CD11b, CD66b, and CD114), metabolism (GLUT-1, LOX1) and immunosuppression (PD1, PD-L1) was carried out within whole blood and within the LDN fraction. Unsupervised analysis of flow cytometry data was performed using visual t-distributed stochastic neighbor embedding (vi-tSNE). A significant increase in the CD11b expression in neutrophils from CF patients during exacerbations was observed compared to neutrophils from stable CF patients or to healthy donors, indicative of a circulating activation state due to an infectious status. The percentage of LDN was not increased in stable CF patients but increased during exacerbations. Analysis of neutrophil subsets using the double CD16/CD62L labeling revealed a significant increase in the CD16high/CD62Llow subset in all CF patients compared to healthy donors. In contrast, an increase in the CD16low/CD62Lhigh subset was observed only in CF patients during exacerbation. Unsupervised analysis identified a PD-L1high/CD114high population that was present in stable CF patients and as well as in CF patients during exacerbations.